Anticorrosion and electromagnetic interference shielding behavior of candle soot‐based epoxy coating. Issue 19 (6th November 2019) - Singh, Priyanka; Chauhan, Sampat Singh; Singh, Gurmeet; Sharma, Moolchand; Singh, V. P.; Vaish, Rahul
ABSTRACT: This article presents candle soot (CS) as anticorrosion coating material for mild steel (MS) in 3.5 wt % of NaCl solution using potentiodynamic polarization and electrochemical impedance spectroscopy. CS is easily available, low‐cost material, and characterized by using X‐Ray diffraction (XRD), Raman spectroscopy, UV–vis spectroscopy, Fourier‐transform infrared (FTIR), and scanning electron microscopy (SEM). CS is superhydrobhobic in nature that helps to prevent corrosion by repelling water molecules from MS surface. The electrochemical results confirmed the prevention in corrosion process for MS using candle soot‐epoxy (CS‐EP) based anticorrosion coatings. The CS‐based coatings displayed outstanding barrier properties in 3.5 wt % of NaCl solution in comparison to the neat EP coating. Different candle CS‐EP coating combinations were tested that exhibited excellent corrosion inhibition performance with highest protection increased up to 98.45% at 0.2 wt % of CS. The surface morphological studies were used to analyze the MS surface conditions in absence and presence of CS‐EP coating in 3.5 wt % of NaCl solution. CS‐EP admixtures were also tested for their shielding effectiveness in the frequency range of 8.2–12.4 GHz and it has been found that on incorporation of 0.2 wt % of CS in EP resin total shielding effectiveness (SET ) increased to −5.3 dB as compared to −0.33 dB for neat EP. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 137, 48675. Abstract :